Molecular medical microbiology - Tang, Yi-Wei (Academic Press, 2015)
The molecular age has brought about dramatic changes in medical microbiology, and great leaps in our understanding of the mechanisms of infectious disease. Molecular Medical Microbiology is the first book to synthesise the many new developments in both molecular and clinical research in a single comprehensive resource. This timely and authoritative three-volume work is an invaluable reference source of medical bacteriology. Comprising more than 100 chapters, organized into 17 major sections, the scope of this impressive work is wide-ranging. Written by experts in the field, chapters include cutting-edge information, and clinical overviews for each major bacterial group, in addition to the latest updates on vaccine development, molecular technology and diagnostic technology. Topics covered include bacterial structure, cell function, and genetics; mechanisms of pathogenesis and prevention; antibacterial agents; and infections ranging from gastrointestinal to urinary tract, centrtal nervous system, respiratory tract, and more.- Resumé vydavatel